Wycliffe in the making: the memoirs of W. Cameron Townsend, 1920-1933 - Steven, Hugh (Harold Shaw Publishers, 1995)
Home sweet home -- Implicit trust -- A companion in lice cracking -- The Chichicastenango twelve -- Testings -- The dark night of the soul -- Joyous service -- The circuitous route -- Back on the home front -- A great loss -- Unexpected supply -- Fellow dreamers -- WInds of change -- Facing battles -- Forging field policies -- Harmony at last -- A formidable challenge -- A most significant moment -- Faith and imagination -- A new epoch -- Goodbye to Guatemala -- New directions